On two new relations between continuous analog signal and discrete-time sequence. (15th May 2022) - Kumar, Abhimanyu
Abstract: In control and measurement theory, signal processing plays a vital role. Since the advent of discrete data processors, the industry is constantly inclined towards them. Thus, the connection between analog signals represented by their discrete-time information is still a captivating research problem for both engineers and mathematicians. This exposition presents two results, one in the transform (Laplace–Z) domain and other in the time domain. These results are supplemented with formal proofs, followed by pedagogical comments.